Health Information Exchange: Practical Overview and Implications for Nursing Practice. (November 2020) - Nahm, Eun-Shim; Schoenbaum, Anna; Behm, Craig; Rowen, Lisa
Abstract : The US healthcare system is moving into a new era of value-based care, which focuses on delivering safer and higher quality care while reducing costs. Health information exchange (HIE) has been a vital component in this process; however, there has been a lack of awareness and use of HIE among nurse leaders, clinicians, and researchers. The purpose of this article is to provide nurses and administrators with a brief overview of HIE and its impact on care delivery, as well as practical applications using specific case examples.